17O-EPR determination of the structure and dynamics of copper single-metal sites in zeolites - Bruzzese, Paolo Cleto; Salvadori, Enrico; Jäger, Stefan; Hartmann, Martin; Civalleri, Bartolomeo; Pöppl, Andreas; Chiesa, Mario (Nature Communications, 2021)
The bonding of copper ions to lattice oxygens dictates the activity and selectivity of copper exchanged zeolites. By 17O isotopic labelling of the zeolite framework, in conjunction with advanced EPR methodologies and DFT modelling, we determine the local structure of single site CuII species, we quantify the covalency of the metal-framework bond and we assess how this scenario is modified by the presence of solvating H216O or H217O molecules. This enables to follow the migration of CuII species as a function of hydration conditions, providing evidence for a reversible transfer pathway within the zeolite cage as a function of the water pressure. The results presented in this paper establish 17O EPR as a versatile tool for characterizing metal-oxide interactions in open-shell systems.
Created from Fastlane, Scopus look-up

Development of Microstructure and Mechanical Properties of TiAl6V4 Processed by Wire and Arc Additive Manufacturing - Elitzer, Daniel; Jäger, Stefan; Höll, Clara; Baier, Daniel; Varga, Rosa; Zaeh, Michael F.; Göken, Mathias; Höppel, Heinz Werner (Advanced Engineering Materials, 2022)
Wire and arc additive manufacturing (WAAM) has the potential to significantly reduce material waste due to the milling of components made of TiAl6V4 (Ti-64). To keep up with the market development, this resource-efficient technology is becoming increasingly important to achieve climate policy goals. Therefore, this study not only focuses on the influence of different process parameters, such as torch and wire feed speed, but also different gas mixtures on the microstructure and related mechanical properties, as well as on the scalability by investigating single- to multilayer welded structures. The wire feed speed is found to have a major influence on the geometry and mechanical properties. The use of different process gases, i.e., argon (Ar), helium (He), and a mixture of 70% He and 30% Ar neither significantly affect the microstructure nor the mechanical properties. It is also found that a solution heat treatment followed by an annealing step degrades mechanical properties, while an ordinary stress-relief heat treatment leads to improved mechanical properties. It is shown that by adapting WAAM process and heat treatment parameters, mechanical properties of additively produced specimens can be achieved, which are fully comparable to milled components.
CRIS-Team Scopus Importer:2022-09-30
Keywords: additive manufacturing; alpha-beta alloys; heat treatments; mechanical properties; microstructures; Ti-64; WAAM

The Structure of Monomeric Hydroxo-C-II Species in Cu-CHA. A Quantitative Assessment - Bruzzese, Paolo Cleto; Salvadori, Enrico; Civalleri, Bartolomeo; Jäger, Stefan; Hartmann, Martin; Poeppl, Andreas; Chiesa, Mario (Journal of the American Chemical Society, 2022)
Using EPR and HYSCORE spectroscopies in conjunction with ab initio calculations, we assess the structure of framework-bound monomeric hydroxo-Cu-II in copper-loaded chabazite (CHA). The species is an interfacial distorted square-planar [(CuOH)-O-II(O-8MRs)(3)] complex located at eight-membered-ring windows, displaying three coordinating bonds with zeolite lattice oxygens and the hydroxo ligand hydrogen-bonded to the cage. The complex has a distinctive EPR signature with g = [2.072 2.072 2.290], (Cu)A= [30 30 410] MHz, and (H)A = [-13.0 -4.5 +11,5] MHz, distinctively different from other Cu-II species in CHA.
CRIS-Team WoS Importer:2022-08-05